2022
DOI: 10.26508/lsa.202201400
|View full text |Cite
|
Sign up to set email alerts
|

ZBTB18 inhibits SREBP-dependent lipid synthesis by halting CTBPs and LSD1 activity in glioblastoma

Abstract: Enhanced fatty acid synthesis is a hallmark of tumors, including glioblastoma. SREBF1/2 regulate the expression of enzymes involved in fatty acid and cholesterol synthesis. Yet, little is known about the precise mechanism regulating SREBP gene expression in glioblastoma. Here, we show that a novel interaction between the co-activator/co-repressor CTBP and the tumor suppressor ZBTB18 regulates the expression of SREBP genes. In line with our findings, metabolic assays and glucose tracing analysis confirm the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The widespread expression of CtBP2 across diverse tissues prompted us to investigate the potential roles of CtBP2 in nonhepatic tissues. Next, we examined pancreatic β-cells and found that CtBP2 is CtBP2 through a CtBP2/liver X receptor (LXR)/ SREBP1 complex, as was further ensured by another independent report 34) . Intriguingly, these CtBP2/ FoxO1 and CtBP2/SREBP1 complex formations were significantly diminished in mouse models of obesity and in human specimens, indicating that liberation of FoxO1 and SREBP1 from CtBP2-mediated repression is one of the key mechanisms underlying the concurrent activation of hepatic gluconeogenesis and lipogenesis in obesity (Fig.…”
Section: Ctbp2 Plays Pivotal Roles In the Pathogenesis Of Obesitymentioning
confidence: 75%
“…The widespread expression of CtBP2 across diverse tissues prompted us to investigate the potential roles of CtBP2 in nonhepatic tissues. Next, we examined pancreatic β-cells and found that CtBP2 is CtBP2 through a CtBP2/liver X receptor (LXR)/ SREBP1 complex, as was further ensured by another independent report 34) . Intriguingly, these CtBP2/ FoxO1 and CtBP2/SREBP1 complex formations were significantly diminished in mouse models of obesity and in human specimens, indicating that liberation of FoxO1 and SREBP1 from CtBP2-mediated repression is one of the key mechanisms underlying the concurrent activation of hepatic gluconeogenesis and lipogenesis in obesity (Fig.…”
Section: Ctbp2 Plays Pivotal Roles In the Pathogenesis Of Obesitymentioning
confidence: 75%
“…Currently, six structurally distinct NNRTIs were approved by FDA for clinical HIV treatment, but the rapid emergence of resistant strains inevitably reduced the effectiveness of existing drugs. The single mutants are mainly composed of L100I, K101E, E138K, K101P, P225H, M230L, K238T, F227L, V106A/M, K103N/S, Y188L/C/H, Y181C/I/V, and G190A/S/E and the double mutants mainly consist of K103N + L100I and K103N + Y181C. New data on HIV drug resistance from Stanford University in 2022 reveal that first-generation inhibitors are partially or completely insensitive to drug-resistant strains, such as Y181C, P236L, and K103N, whereas second-generation NNRTIs were significantly less susceptible to mutant strains such as K101E, E138K, and Y181V . As two well-known FDA-approved second-generation NNRTIs, etravirine (ETR, 1 ) and rilpivirine (RPV, 2 ), structurally characterized by a typical diarylpyrimidine (DAPY) moiety, possessed excellent broad-spectrum antiviral activity toward wild-type (WT) HIV-1 and several clinically mutant strains .…”
Section: Introductionmentioning
confidence: 99%
“…8−10 New data on HIV drug resistance from Stanford University in 2022 reveal that first-generation inhibitors are partially or completely insensitive to drug-resistant strains, such as Y181C, P236L, and K103N, whereas second-generation NNRTIs were significantly less susceptible to mutant strains such as K101E, E138K, and Y181V. 11 As two well-known FDA-approved second-generation NNRTIs, etravirine (ETR, 1) and rilpivirine (RPV, 2), structurally characterized by a typical diarylpyrimidine (DAPY) moiety, possessed excellent broad-spectrum antiviral activity toward wild-type (WT) HIV-1 and several clinically mutant strains. 12 Unfortunately, their high cytotoxicity (CC 50 = ∼5 μM) and low selectivity index (SI ≈ 1000) limited their long-term uses and clinical efficacy.…”
Section: ■ Introductionmentioning
confidence: 99%